2021
DOI: 10.1021/acssynbio.1c00017
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework for Identifying Promoter Sequences in Nonmodel Organisms Using RNA-seq Data Sets

Abstract: Engineering microorganisms into biological factories that convert renewable feedstocks into valuable materials is a major goal of synthetic biology; however, for many nonmodel organisms, we do not yet have the genetic tools, such as suites of strong promoters, necessary to effectively engineer them. In this work, we developed a computational framework that can leverage standard RNA-seq data sets to identify sets of constitutive, strongly expressed genes and predict strong promoter signals within their upstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The difference in the activity observed here compared to prior analyses could be due to E. coli strain variations since we measured fluorescence in DH10B while others have used DH5α. Recently, BBa_J23119 was demonstrated to display high activity in the Gammaproteobacterial methanotroph Methylotuvimicrobium buryatense 5GB1C, but it was suggested that other promoters in the series may not function in methanotrophs due to a lack of measured BBa_J23112 and BBa_J23117 activity in M. buryatense [ 39 ]. Notably, these two promoters have limited activity in E. coli , and we observed low activity of BBa_J23117 in M. capsulatus Bath and M. trichosporium OB3b ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the activity observed here compared to prior analyses could be due to E. coli strain variations since we measured fluorescence in DH10B while others have used DH5α. Recently, BBa_J23119 was demonstrated to display high activity in the Gammaproteobacterial methanotroph Methylotuvimicrobium buryatense 5GB1C, but it was suggested that other promoters in the series may not function in methanotrophs due to a lack of measured BBa_J23112 and BBa_J23117 activity in M. buryatense [ 39 ]. Notably, these two promoters have limited activity in E. coli , and we observed low activity of BBa_J23117 in M. capsulatus Bath and M. trichosporium OB3b ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with the rapid development of genomics technology, the genomic library screening method has become a common method for screening promoters, and researchers have screened a series of constitutive or inducible promoters from a variety of bacteria using RNA-seq methods. , Wherein a constitutive promoter is a class of promoters that are not controlled by any regulator or growth conditions and where the expression level of the gene is usually constant at a certain level. Kong et al validated a series of constitutive promoters by screening genes that were stably expressed during different growth periods under different culture conditions via RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, promoter-predicted platforms will help select optimal promoter sequences, and hybridizations are contributed to building a mutated library (Vogl et al 2018 , Cazier et al 2021 ). A computational framework was developed to predict promoter regions according to RNA-seq data sets in M. buryatense 5GB1 (Wilson et al 2021 ). Given this, metabolic networks based on promoter regulation can be easily predicted and established.…”
Section: Promoter Engineeringmentioning
confidence: 99%